El crédito documentario, su regulación y funcionamiento - Calderón Burneo, Ernesto (Revista de Derecho, 2019)
This paper deals with the study of the Documentary Credit as a mechanism of payment in international trade transactions. The main objective is to explain, in general, a number of issues relating to this figure by presenting the reader with the relevant information with regards to the payment mechanism and the roles of the individuals involved in the contract itself. This paper is by no means an exhaustive study about the Documentary Credit but a brief approach to a subject rarely addressed in national Law and the importance of which is not always highlighted.
Keywords: Documentary Credit; payment; international sale of goods; issuing bank; standby letters of credit; back-to-back credits